(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Learning outcomes of medical students are the achievements realized upon the completion of a study process. These outcomes are influenced by various factors. Investigating the learning outcomes of medical students, as well as related factors, is necessary to implement timely adjustments and improve the quality of training. Objective: To determine the prevalence of 4th-year medical students with unsatisfactory learning outcomes and to investigate factors associated with unsatisfactory learning outcomes at Nguyen Tat Thanh University during the academic year 2024-2025. Methods: A cross-sectional descriptive study was conducted on 551 4th-year medical students who had completed the curriculum during the period from December 2, 2024, to January 10, 2025. Results: The prevalence of students with unsatisfactory learning outcomes was 8%. Related factors included: international students, lack of desire to study medicine, lack of self-study capability, poor concentration during lectures, not reading materials guided by the lecturer, not studying in groups, missed subjects. Conclusions: Learning outcomes of 4th-year medical students at Nguyen Tat Thanh University mostly met the requirements (>90%). Factors related to unsatisfactory learning outcomes are modifiable. The study serves as a basis for making appropriate adjustments to improve the learning outcomes of students in the following years.